Modelling perceived service quality and turnover intentions in gender-segregated environments - Olya, Hossein; Taheri, Babak; Farmaki, Anna; Gannon, Martin Joseph (My University, 2021)
This study extends current understanding of how gender shapes value co-creation, perceived service quality and turnover intention within health and fitness clubs. Survey responses were collected from 485 fitness club customers in Iran. Partial least squares structural equation modelling (PLS-SEM) was deployed to demonstrate the effects of predictor variables while fuzzy-set qualitative comparative analysis (fsQCA) was used to identify combinations of value co-creation behaviours capable of predicting model outcomes. Necessary condition analysis (NCA) was also employed to identify the value co-creation factors required to achieve low turnover intentions and high service quality perceptions. Results reveal the moderating role of gender in shaping the complex combinations of value co-creation factors leading to low turnover and high perceived quality; fsQCA findings demonstrate how this differs between male and female consumers. NCA findings suggest that fitness club managers should foster an interactive environment through advocacy programmes, promoting responsible behaviours and boosting tolerance, to encourage both male and female customers to participate in co-creation processes. This is the first empirical study to apply complexity theory to explore whether service quality perceptions and turnover intentions vary across gender via structural and configurational modelling.
Keywords: Advocacy; Complexity theory; Gender; Sports marketing; Value co- creation